The effect of regulating the proportion of track students on the cognitive learning outcome of natural science courses in single-track schools - Al-Shahrani, Mohammed Mufarrih (Journal of Educational and Psychological Sciences, 2023)
The aim of this research is to identify the extent of the effect of regulating the percentage of track students on the freedom of students to choose the specialization track, and the reality of this effect on the cognitive learning outcome of the joint courses and the courses of the natural sciences track. After conducting the interview with the research sample individuals and obtaining the records of the sample scores from its official source, the Noor system, And the arbitration of the research tool and verification of its validity and stability; The analysis card was applied to the scores of the sample that represents all members of the research community consisting of the second grade of secondary school in Umm Al-Qura, courses in the educational sector of Al-Sha`f in Asir region (n = 35) during the first semester of the academic year 1441 AH, then the necessary statistical analyzes were conducted, and the results showed the following: 1-The effect of regulating the percentage of track students on students’ freedom to choose a specialization track, as this regulation forced (29.54%) of the total number of the sample to join a specialized track that does not correspond to their capabilities and tendencies. 2-The low percentage of the total scores of the compulsory courses of the natural sciences track for the individuals of the sample who are forced to join a specialized track that does not correspond to their capabilities and tendencies, as it reached (46.75%), compared to (70.5%) of the total scores of the combined courses of this sample. 3- An increase in the percentage of total scores for the compulsory courses of the natural sciences track for the sample members enrolled in a specialized track that corresponds to their capabilities and tendencies, reaching (78.75%), compared to (92.5%) for the total scores for the joint courses of this sample. In light of the results, several recommendations were recommended, the most important of which are: the need to review the regulation of the percentage of track students in the course system after it was circulated to the secondary level, to ensure that students join the specialized track that is compatible with their capabilities and tendencies.